Do the joint effects of size, shape and ecocorona influence the attachment and physical eco(cyto)toxicity of nanoparticles to algae? - Abdolahpur Monikh, Fazel; Arenas-Lago, Daniel; Porcal, Petr; Grillo, Renato [UNESP]; Zhang, Peng; Guo, Zhiling; Vijver, Martina G.; J. G. M. Peijnenburg, Willie (Taylor & Francis, 2020)
We systematically investigated how the combinations of size, shape and the natural organic matter (NOM)-ecocorona of gold (Au) engineered nanoparticles (ENPs) influence the attachment of the particles to algae and physical toxicity to the cells. Spherical (10, 60 and 100 nm), urchin-shaped (60 nm), rod-shaped (10 × 45, 40 × 60 and 50 × 100 nm), and wire-shaped (75 × 500, 75 × 3000 and 75 × 6000 nm) citrate-coated and NOM-coated Au-ENPs were used. Among the spherical particles only the spherical 10 nm Au-ENPs caused membrane damage to algae. Only the rod-shaped 10 × 45 nm induced membrane damage among the rod-shaped Au-ENPs. Wire-shaped Au-ENPs caused no membrane damage to the algae. NOM ecocorona decreased the membrane damage effects of spherical 10 nm and rod-shaped 10 × 45 nm ENPs. The spherical Au-ENPs were mostly loosely attached to the cells compared to other shapes, whereas the wire-shaped Au-ENPs were mostly strongly attached compared to particles with other shapes. NOM ecocorona determined the strength of Au-ENPs attachment to the cell wall, leading to the formation of loose rather than strong attachment of Au-ENPs to the cells. After removal of the loosely and strongly attached Au-ENPs, some particles remained anchored to the surface of the algae. The highest concentration was detected for spherical 10 nm Au-ENPs followed by rod-shaped 10 × 45 nm Au-ENPs, while the lowest concentration was observed for the wire-shaped Au-ENPs. The combined effect of shape, size, and ecocorona controls the Au-ENPs attachment and physical toxicity to cells.
Keywords: cellular association; Membrane damage; rod-shaped Au-ENPs; spherical Au-ENPs; wire-shaped Au-ENPs